THE DURABILITY OF THE REHABILITATION OF RIGID ROAD STRUCTURES ACCORDING TO TRAFFIC VALUES - Gavris Ovidiu (Fiabilitate şi Durabilitate)
The article presents a comparative study of effort and strain state of a rigid road structure (concrete cement pavement), rehabilitated (reinforced) in two ways: - full milling of the concrete slabs followed by a reinforcement with layers of crushed stone and asphalt concrete. - cracking the concrete slabs and covering them with layers of crushed stone and asphalt concrete. The purpose of this article is to present and compare the two modes of intervention on cement concrete road structures, so that the rehabilitated system will behave properly in service. This study also offers design engineers an image and potential solutions for intervention when dealing with these types of structures.